PENGARUH SLOW STROKE BACK MASSAGE TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RSUD PAKUHAJI KABUPATEN TANGERANG - Destiawan Eko Utomo; Ardina Nurfadillah Febianah; Zahrah Maulidia Septimar (Nusantara Hasana Berdikari, 2022)
Hypertension is a chronic condition in which the blood pressure in the arterial wall increases, namely systolic blood pressure > 140 mmHg and diastolic > 90 mmHg, non-pharmacological treatment, namely complementary therapy in the category of manipulative and body based therapies, can reduce blood pressure, namely massage therapy with slow intervention methods stroke back massage This study aims to determine the effect of slow stroke back massage on changes in blood pressure in hypertensive patients at Pakuhaji Hospital Tangerang Regency. Quantitative research with Quasi Experimental design: Two group pretest-posttest design with Non Random (Non Probability) sampling technique with Accidental Sampling as many as 40 respondents. From the statistical test results paired sample t-test in the experimental group systolic blood pressure decreased by 10.4 mmHg and diastolic blood pressure decreased by 14.85 mmHg while the control group decreased systolic blood pressure by 3.25 mmHg and diastolic blood pressure decreased by 2. 75 mmHg The results of the mean value in the experimental group and the control group for systolic and diastolic blood pressure obtained a significance value (2-tailed) 0.000 <0.05 so it can be concluded that there is a difference in the average pretest and posttest values ​​in the experimental group and the control group. The Effect of Slow Stroke Back Massage on Blood Pressure Changes in Hypertensive Patients at Pakuhaji HospitaL Tangerang.